2009
DOI: 10.1007/978-94-007-0224-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction, Positive Youth Development, and Problem Behaviour Among Chinese Adolescents in Hong Kong

Abstract: This paper examines the relationships among life satisfaction, positive youth development, and problem behaviour. A total of 7,975 Secondary One students (4,169 boys and 3,387 girls; with most aged 12) of Chinese ethnicity recruited from 48 schools responded to validated measures of life satisfaction, positive youth development and problem behaviour. While life satisfaction was positively correlated with different measures of positive youth development, these measures were negatively correlated with measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 52 publications
3
32
0
1
Order By: Relevance
“…Parental factors were significant predictors of emotional and behavioural problems with poor parent–adolescent relationship the strongest predictor of risk. Previous studies have suggested that parent–child interaction is a significant predictor for behaviour outcome (Hemphill & Littlefield ) and children experiencing parent–child conflicts have poor mental health (Sun & Shek ). It is also reported that that good parent–child communications decrease the prevalence of delinquency (Cernkovich & Giordano ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parental factors were significant predictors of emotional and behavioural problems with poor parent–adolescent relationship the strongest predictor of risk. Previous studies have suggested that parent–child interaction is a significant predictor for behaviour outcome (Hemphill & Littlefield ) and children experiencing parent–child conflicts have poor mental health (Sun & Shek ). It is also reported that that good parent–child communications decrease the prevalence of delinquency (Cernkovich & Giordano ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, negative life events in the family have been reported to increase the risk for psychopathology in adolescents (Harland et al . ) and parent–child conflicts to be predictive of adolescent behavioural problems (Hemphill & Littlefield ; Sun & Shek ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a sampling number of 7,975 junior secondary-school students in Hong Kong, Sun and Shek (2010) found that 25.8 % of respondents had drank, 11.4 % involved with vandalism, 10 % assaulted, 6.7 % ran away from home, 6.2 % truanted, and 3.4 % had sexual relationships with others in the past 6 months. In particular, 19.4 % of the respondents reported that they had committed vandalism, 18.3 % truanted, 13.1 % smoked or drank, 11 % were involved with violent behaviors, 3 % ran away from home, and 1.4 % had sexual relationships with others.…”
Section: Discussionmentioning
confidence: 99%
“…High SWLS scores indicate a more positive self‐evaluation of subjective well‐being. Sample items include, “In most ways my life is close to my ideal”, and, “If I could live my life over, I would change almost nothing.” The internal consistency of the SWLS was reported to be at an acceptable level in recent studies with Hong Kong Chinese participants (ranging from 0.74 to 0.87; Chan, ; Shek, ; Sun & Shek, ). Similarly, the α coefficient of this study was 0.84, which was regarded to indicate a high internal consistency.…”
Section: Methodsmentioning
confidence: 98%